A five-center redox system: molecular coupling of two noninnocent imino-o-benzoquinonato-ruthenium functions through a pi acceptor bridge - Das, Atanu Kumar; Sarkar, Biprajit; Fiedler, Jan; Zális, Stanislav; Hartenbach, Ingo; Strobel, Sabine; Lahiri, Goutam Kumar; Kaim, Wolfgang (Journal of the American Chemical Society, 2009)
Combining the concepts of noninnocent behavior of metal/ligand entities and the coupling of redox-active moieties via an electronically mediating bridge led to the synthesis and the structural, electrochemical, and spectroscopic characterization of [Cl(Q)Ru(mu-tppz)Ru(Q)Cl](n) where Q(o) is 4,6-di-tert-butyl-N-phenyl-o-iminobenzoquinone and tppz(o) is 2,3,5,6-tetrakis(2-pyridyl)pyrazine, the available oxidation states being Ru(II,III,IV), Q(o,*-,2-), and tppz(o,*-,2-). One-electron transfer steps between the n = (2-) and (4+) states were studied by cyclic voltammetry and by EPR, UV-vis-NIR spectroelectrochemistry for the structurally characterized anti isomer of [Cl(Q)Ru(mu-tppz)Ru(Q)Cl](PF(6))(2), 2(PF(6))(2), the only configuration obtained. The combined investigations reveal that 2(2+) is best described as [Cl(Q(*-))Ru(III)(mu-tppz(o))Ru(III)(Q(*-))Cl](2+) with antiferromagnetic coupling between the ruthenium(III) and the iminosemiquinone components at each end. A metal-based spin as evident from large g factor anisotropy (EPR) and an intense intervalence absorption band at 1850 nm in the near-infrared (NIR) suggest that oxidation occurs at both iminosemiquinones to yield two Ru(II,III)-bonded quinones, implying redox-induced electron transfer. Reduction takes place stepwise at the metal centers yielding iminosemiquinone complexes of Ru(III,II) as evident from radical complex EPR spectra with small (99,101)Ru hyperfine contributions. After complete metal reduction to ruthenium(II) the bridging ligand tppz is being reduced stepwise as apparent from typical NIR absorption bands around 1000 nm and from small g anisotropy of the monoanion [Cl(Q(*-))Ru(II)(mu-tppz(*-))Ru(II)(Q(*-))Cl](-). A structure-based DFT calculation confirms the Ru-Cl character of the HOMO and the iminoquinone-dominated LUMO and illustrates the orbital interaction pattern of the five electron transfer active components in this new system.